2018
DOI: 10.1038/nm.4485
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Zika virus infection as a silent pathology with loss of neurogenic output in the fetal brain

Abstract: Zika virus (ZIKV) is a flavivirus with teratogenic effects on the fetal brain, but the spectrum of brain injury is unknown, particularly when ultrasound imaging is normal. In a pregnant pigtail macaque (Macaca nemestrina) model, we demonstrate that ZIKV injury to the fetal brain was significant even in the absence of microcephaly and is clinically challenging to detect. A common and subtle injury pattern was identified including: 1) periventricular T2-hyperintense foci and loss of fetal non-cortical brain volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
147
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(186 citation statements)
references
References 51 publications
(47 reference statements)
18
147
0
Order By: Relevance
“…Similar to the fetal brain injury observed after maternal ZIKV infection in a pigtail macaque model as well as congenital ZIKV syndrome in humans (2, 26, 62, 63), our analysis of postnatal ZIKV infection in RM infants revealed inflammation, reactive astrocytes, gliosis in the grey and white matter, axonal injury, and apoptosis in the brain and spinal cord. In particular, the consistent finding of astrogliosis between the infant infection model described here and fetal infection illustrates a common pathology of postnatal and in utero ZIKV infection (63). In our model, ZIKV RNA was not detected in the brain regions showing increased apoptosis and gliosis, suggesting these abnormalities may be due to an indirect inflammatory mechanism rather than direct cytopathic effect of the virus.…”
Section: Discussionsupporting
confidence: 76%
“…Similar to the fetal brain injury observed after maternal ZIKV infection in a pigtail macaque model as well as congenital ZIKV syndrome in humans (2, 26, 62, 63), our analysis of postnatal ZIKV infection in RM infants revealed inflammation, reactive astrocytes, gliosis in the grey and white matter, axonal injury, and apoptosis in the brain and spinal cord. In particular, the consistent finding of astrogliosis between the infant infection model described here and fetal infection illustrates a common pathology of postnatal and in utero ZIKV infection (63). In our model, ZIKV RNA was not detected in the brain regions showing increased apoptosis and gliosis, suggesting these abnormalities may be due to an indirect inflammatory mechanism rather than direct cytopathic effect of the virus.…”
Section: Discussionsupporting
confidence: 76%
“…At the present moment, it is too early to assess cognitive abilities in these children [6, 23, 24]. Adams et al [25], in a study in macaques, have demonstrated that even in the absence of microcephaly, the teratogenic action of ZIKV infection in the fetal brain is substantial and has long-lasting effects. These effects on the fetal brain include loss of fetal noncortical brain volume, injury to the ependymal epithelium, and loss of late fetal neuronal progenitor cells.…”
Section: Zikv Infection During Pregnancy and Its Effectsmentioning
confidence: 99%
“…Three of the monkeys also received a monoclonal dengue virus antibody to model the effects of pre-exposure to another flavivirus. However, as Adams Waldorf et al 7 acknowledge, the small number of monkeys and multiple treatment conditions in this experimental design preclude any definitive conclusion about whether dengue antibodies potentiate the deleterious effects of ZIKV infections. Following inoculation with ZIKV, none of the fetuses developed microcephaly, and weekly ultrasounds did not reveal any gross fetal abnormalities until gestational day 100.…”
mentioning
confidence: 97%
“…Congenital Zika syndrome has now been defined as a spectrum of abnormalities that range far beyond microcephaly to include other severe impairments, such as craniofacial disproportion, ocular anomalies, and intracranial calcifications, but the nature and extent of potential Zika-related pathology is still not fully understood. Here, Adams Waldorf et al 7 further study offspring of ZIKV-infected pigtail macaques and identify indications of neurological damage in the absence of microcephaly.…”
mentioning
confidence: 99%
See 1 more Smart Citation